MICROBIAL TRANSLOCATION, TOLL-LIKE RECEPTOR 4, AND KAEMPFERIA GALANGA AS NEW PERSPECTIVES IN DENGUE PATHOGENESIS AND THERAPY: A REVIEW - JATMIKO, SAFARI WAHYU; AISYAH, RIANDINI (International Journal of Applied Pharmaceutics, 2025)
Dengue Virus Infection (DVI) is a major health concern in tropical regions, including Indonesia, with symptoms ranging from mild to severe. Genetic factors, such as Toll-Like Receptor 4 Single-Nucleotide Polymorphisms (TLR4 SNPs), influence disease severity. Severe DVI is associated with a cytokine storm and elevated Lipopolysaccharides (LPS), suggesting microbial translocation due to increased intestinal permeability. Antibiotics reduce gut bacterial populations but may worsen permeability. Kaempferia galanga, an herbal medicine with antimicrobial and anti-inflammatory properties, presents a potential therapeutic approach. This review explores the role of microbial translocation and Toll-like receptors in DVI pathogenesis and the potential of Kaempferia galanga in mitigating these effects. A narrative review was conducted using literature from PubMed, Scopus, and Google Scholar with the keywords "microbial translocation," "TLR4," "Kaempferia galanga," "herbal medicine," and "immune modulation" without publication year restrictions. DVI triggers immune cell activation and proinflammatory cytokine production, leading to increased intestinal permeability and microbial translocation. LPS in the bloodstream activates immunocytes via TLR4, amplifying cytokine production and worsening inflammation. While TLR4 SNPs do not directly influence this process, TLR4 expression is involved. Kaempferia galanga exhibits antibacterial and anti-inflammatory properties that reduce intestinal permeability, thereby limiting microbial translocation. This, in turn, decreases TLR4 activation by LPS, mitigating the cytokine storm. DVI-induced cytokine production increases intestinal permeability, facilitating microbial translocation and systemic inflammation. LPS activates TLR4, driving cytokine release independently of TLR4 SNPs. Kaempferia galanga may inhibit this process through its antimicrobial and anti-inflammatory properties, offering a promising therapeutic strategy.